The Use of Paper Toys in Supporting Fine Motor Development of Children with Moderate Mental Retardation - Sofia Esterina Pong; Erma Retnaningtyas; Eva Agustina Yalestyarini (PT. Griya Eka Sejahtera, 2020)
Background: Mentally retarded children are children who have intellectual decline. Children with mental retardation cannot coordinate well with small muscles or fine motor parts, for example: folding fingers, and so on. Method: This research uses Pre-Experiment One Group Pre Test Post Test Design. The sample of mental retardation in SLB C1 Putera Asih Kediri City was 30 respondents using purposive sampling technique to meet the inclusion and exclusion criteria, there were 28 respondents. The independent variable is paper toys and the dependent variable is the fine motor skills of children with moderate mental retardation. The instrument is an observation sheet to determine the effect between the variables used by the Wilcoxon test with a significant level of 0.05. Results The results of the study, before being given paper toys as many as 20 (67%) children experienced inappropriate fine motor development. Fine motor development of moderately mentally retarded children after being given paper toys as many as 21 children (48%) children experienced good fine motor development. The results of the statistical test show a significant value with a p value of 0.000 which means p value <0.005 so that H0 is rejected. Conclusion: the use of paper toys at SLB C1 Putera Asih, Kediri City shows that there is an influence between the use of paper toys and fine motor development, because paper toys can make children concentrate, explore or stimulate children to coordinate their small muscles or fine motor skills